Resíduo Industrial de Andiroba como Fonte de Extrato Fotoprotetor: Obtenção e Caracterização - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
The Amazon hosts unique biodiversity and has great potential for the sustainable use of its natural resources. Carapa guianensis (andiroba), widely used in the cosmetic and pharmaceutical industries, generates a large amount of solid waste after the extraction of its fixed oil, which is often discarded without proper utilization. This study evaluated the photoprotective potential of extracts obtained from andiroba industrial waste, aiming to promote sustainable reuse and add value to this byproduct. The extracts were obtained using Soxhlet extraction and characterized for total phenol content, flavonoids, and sun protection factor (SPF) using UV-Vis spectrophotometry. The results demonstrated that the extracts exhibit high photoprotective potential, with SPF values of 38.27 for the bark and 49.96 for the residual cake, comparable to commercially available medium-protection sunscreens. None of the extracts showed a reaction for flavonoids, suggesting that other bioactive compounds, such as limonoids and fatty acids, may contribute to UV radiation absorption. Additionally, repurposing this waste may serve as a sustainable alternative to synthetic sunscreen filters, reducing environmental impacts and providing an accessible product to the population. Thus, this study highlights the importance of utilizing agro-industrial byproducts for the development of eco-friendly and innovative cosmetic formulations.
Resíduo Industrial de Andiroba como Fonte de Extrato Fotoprotetor: Obtenção e Caracterização
Keywords: Carapa guianensis; Fotoproteção; Resíduos industriais; Polifenois; Sustentabilidade; CNPQ:: CIÊNCIAS DA SAÚDE; CNPQ:: CIÊNCIAS DA SAÚDE